Development of Digital Library Based Responsive Web Using CMS Wordpress.org - Shinta Khatulistiwa; Aulia Fashanah Hadining; Dene Herwanto (Jurnal Rekayasa Sistem & Industri, 2020)
Library is one of the information facilities that functions to open the knowledge. Currently there arevarious types of libraries ranging from conventional to digital. The Faculty of Engineering's ReadingRoom needs to be developed into a Digital Library to make it more effective and efficient in the deliveryand search of libraries. Also, a repository needs to be made so that the scientific papers are not only in printformat. The variety of devices at this time caused user interface problems later. The solution is developingDigital Library with a responsive web-based. The method used in this research is a Prototype. Reasons touse this method is because during the development process client couldn’t deliver the completerequirement needs. They can’t provide a detailed definition of the specifications, requirements, andobjectives of the system. Then there’s no complete metadata for this research. In addition, the user can’t beinvolved in all stages of development. Wordpress.org is used as a software that builds and manages webinteractions. The results of this research are the successful development that makes the delivery and searchof libraries effective and efficient on various types of devices